Habits, Customs and Community Beliefs about Malaria and Its Vector (Anopheles sp.) in Vistahermosa (Meta-Colombia) (2017)
Background: Malaria is endemic in Colombia and still a major problem in public health. This study aims to describe the community knowledge, attitudes and practices related to malaria and its vector Anopheles sp. In Vistahermosa (Meta). Methods: This was a descriptive cross-sectional study using a KAP form for adult residents who provided informed consent. The sample was calculated with 95% confidence level, 5% error rate and expected frequency of 10%. Sociodemographic information, knowledge, attitudes and practices about the disease and the vector, and perception of Health Department actions were recorded. Descriptive statistics for the collected data were recorded, and 95% confidence intervals were included. Results: In total, 120 surveys were conducted. A total of 40% of the respondents had had malaria, and 88.33% considered the disease a problem. A total of 13.33% did not complete treatment. A total of 50.83% of the respondents reported that each person was responsible for prevention, 25% reported that prevention was the responsibility of the Health Department, and 5% reported that prevention was the responsibility of the community. There was low participation and community appropriation (2.5%), and 12.50% of the respondents did nothing to prevent mosquito bites. There was confusion between the vector of malaria (Anopheles) and Aedes aegypti. There is still a lack of knowledge of the transmission mechanisms of malaria. Conclusion: Health is not the sole responsibility of health agencies but is a point of convergence between communities and government entities, which should design effective prevention and control programs. © ADR Journals 2017. All Rights Reserved.